2014
DOI: 10.1002/tox.22006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of co-exposure to 2,3,7,8-tetrachlorodibenzo-p-dioxin and polychlorinated biphenyls on nonalcoholic fatty liver disease in mice

Abstract: 2,3,7,8-Tetrachlorodibenzo-p-dioxin (TCDD) and polychlorinated biphenyls (PCBs) are persistent organic pollutants which coexist in environment, and human are co-exposed to these chemicals. Our present study was aimed to investigate the possible enhanced nonalcoholic fatty liver disease (NAFLD) in ApoE 2/2 mice co-exposed to TCDD and PCBs and to reveal the potential mechanisms involved in. Male ApoE 2/2 mice were exposed to TCDD (15 lg/kg) and Aroclor1254 (55 mg/kg, a representative mixture of PCBs) alone or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…Immune responses play an important role in MLD-STZ-induced diabetes (Gao et al, 2013; Barbu-Tudoran et al, 2013; Yaochite et al, 2013), and in TCDD-mediated toxicity (Mandal, 2005; Shan et al, 2014). Thus, flow cytometric analysis of splenocyte differentials was undertaken.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Immune responses play an important role in MLD-STZ-induced diabetes (Gao et al, 2013; Barbu-Tudoran et al, 2013; Yaochite et al, 2013), and in TCDD-mediated toxicity (Mandal, 2005; Shan et al, 2014). Thus, flow cytometric analysis of splenocyte differentials was undertaken.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the appearing anti-diabetic effects, TCDD has been shown to promote a host of adverse metabolic diseases, including non-alcoholic fatty liver disease (NAFLD), a wasting-like syndrome, and cancer in lab animals. These effects are possibly mediated through the immunotoxicity (Mandal, 2005; Shan et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…More than two thirds of the American population is at risk for developing obesity‐associated NAFLD, which is the hepatic arm of metabolic syndrome. Several studies have identified potential interactions between environmental chemicals and experimental NAFLD . Although the mechanisms are incompletely understood, it is likely that these environmental chemicals enhance pathologic responses (e.g., inflammation) and/or sensitize the hepatocytes to injury.…”
Section: Discussionmentioning
confidence: 99%
“…For example, pre-treatment of rats with TCDD led to the appearance of NAFLD, whilst DEHP reduced the TCDD-induced phenotype 104 . Similarly, the combination of TCDD and Aroclor 1254 seemed to enhance NAFLD in mice, compared with treatment with either EDC alone 105 . Although this approach has been applied in only a few experimental settings, the data are extremely relevant to humans, where exposure to more than one EDC during development and over the course of a lifetime may occur.…”
Section: Liver Fat Metabolism and Edcsmentioning
confidence: 92%